The Role of Promyelocytic Leukemia Nuclear Bodies During HPV Infection - Guion, Lucile G.; Sapp, Martin (Frontiers in Cellular and Infection Microbiology, 2020)
Promyelocytic leukemia (PML) nuclear bodies (NBs) are highly dynamic subnuclear structures. Their name giving major component, PML protein, is essential for their formation. PML is present in many different isoforms due to differential splicing, which seem to contribute differently to PML NBs function. Sp100 and DAXX are also permanently residing in these structures. PML NBs disassemble in mitosis to form large cytoplasmic aggregates and reassemble after completion of cell division. Posttranslational modifications such as SUMOylation play important roles for protein association with PML NBs. In addition to the factors permanently associated with PML NBs, a large number of proteins may transiently reside in PML NBs dependent on cell stage, type, and condition. PML NBs have been indirectly implicated in a large number of cellular processes including apoptosis, transcriptional regulation, DNA repair and replication. They are considered hot spots for posttranslational modifications and may serve as readily accessible protein depots. However, a precise function has been difficult to assign. Many DNA viruses target PML NBs after entry often resulting in reorganization of these subnuclear structures. Antiviral activity has been assigned to PML NBs partially based on the observation that PML protein is an interferon stimulated gene. In contrast, human papillomavirus (HPV) infection requires the presence of PML protein suggesting that PML NBs may be essential to establish infection. This review will summarize and discuss recent advances in our understanding of the role of PML NBs and individual protein components in the establishment of HPV infection.